Ananda Putri Handayani The Effect of Smash Drill Training Using Visual Cues on Quick Smash Tipple Skills in Athletes Aged 15-19 Years - Handayani, Ananda Putri; Wahyudi, Agung (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to analyze the effect of drill smash exercises using visual cues on the improvement of quick smash skills in volleyball athletes aged 15–19 years. The main premise of the study is that the skill of quick smash is determined not only by the repetition of the technique, but also by the athlete's ability to respond to visual stimuli, regulate jump timing, coordinate eye-hand movements, and direct punches accurately. The research uses a quantitative approach with a one group pretest-posttest design. The research sample consisted of six athletes from the Tunas Tugumuda Semarang Volleyball Club who were selected through purposive sampling techniques. Treatment was given in the form of a quick smash drill exercise based on visual cues for 14 meetings. The research instrument used a quick seesaw's smash accuracy test with 10 experiments based on the target zone. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, paired sample t-test, and effect size. The results of the descriptive analysis showed an increase in the average score from the pretest by 24.50 to 37.83 in the posttest. The normality test showed that the data was distributed normally, so the hypothesis test was carried out using a paired sample t-test. The results of the t-test showed a significant difference between the pretest and the posttest with a p< value of 0.001. In addition, the effect size results showed a huge influence, which indicated that exercise had a strong practical impact on the improvement of athletes' skills. Thus, the research hypothesis is accepted, namely that drill smash exercises using visual cues have a significant effect on improving quick smash skills to jump. These findings suggest that the integration of drill drills and visual cues can be an effective, applicative, and relevant training strategy for the development of attack skills of young volleyball athletes. Keywords: drill exercises; visual cues; Smash Quick Seesaw; ball; motor skills.